Analyzing Translation Strategies Used in Komedi Kacau (Comedy Chaos) - Jehoshua Yeremia Putra Sutanto; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study discusses the translation strategies employed by the translator in translating the web-series of Komedi Kacau (Comedy Chaos). The translation strategies used in the web-series were qualitatively analyzed using the theory of Mona Baker (2018). The translation strategies employed by Baker (2018) were Equivalence at Word Level which consist of Morpheme and Lexical Meaning. Also, the other translation strategies proposed by Baker (2018) were Equivalence Above Word Level which consist of Collocation and Idioms. The result of the translation is affected by the strategies and the visual context. Although there are some errors in the translation, the translator can still maintain the meaning of the original text and maintain the context spoken by each character in the Komedi Kacau (Comedy Chaos) web-series.